Cascading effects of childhood abuse on physical health issues in later adulthood through trait anxiety and poor daily sleep quality. (October 2021) - Tracy, Eunjin Lee; Tracy, Cory T; Kim, Jichan J; Yang, Rumei; Kim, Eunjung
The purpose of this study was to investigate the mediating roles of trait anxiety and daily sleep quality between childhood abuse and physical health issues later in adulthood by utilizing the Midlife in the United States Study ( n = 281; Mage = 56.38 in wave 2 and Mage = 62.57 in wave 3). Individuals who reported a higher level of childhood abuse reported a higher level of trait anxiety and a lower level of daily sleep quality, leading to an increase in physical health issues. The results highlight the cascading effects of childhood abuse on serious health consequences over the life span.